2015
DOI: 10.3389/fncel.2015.00219
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term NMDAR antagonism correlates reduced astrocytic glutamate uptake with anxiety-like phenotype

Abstract: The role of glutamate N-methyl-D-aspartate receptor (NMDAR) hypofunction has been extensively studied in schizophrenia; however, less is known about its role in anxiety disorders. Recently, it was demonstrated that astrocytic GLT-1 blockade leads to an anxiety-like phenotype. Although astrocytes are capable of modulating NMDAR activity through glutamate uptake transporters, the relationship between astrocytic glutamate uptake and the development of an anxiety phenotype remains poorly explored. Here, we aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…There is evidence, however, for the expression of functional NMDA receptors on astrocytes in upper layers of the cortex (Mehina, Murphy‐Royal, & Gordon, ). As such the effects of prolonged NMDA receptor antagonism on glutamate transporter function used in Zimmer et al () could be mediated by direct effects of memantine on astrocytic NMDA receptors. In agreement with the data from Zimmer et al (), injection of a dihydrokainate into the prefrontal cortex of rats, to block glutamate uptake, was found to be sufficient to drive anhedonia‐like behaviors in multiple studies (Bechtholt‐Gompf et al, ; Cui et al, ; John et al, ; Lee, Gaskins, Anand, & Shekhar, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence, however, for the expression of functional NMDA receptors on astrocytes in upper layers of the cortex (Mehina, Murphy‐Royal, & Gordon, ). As such the effects of prolonged NMDA receptor antagonism on glutamate transporter function used in Zimmer et al () could be mediated by direct effects of memantine on astrocytic NMDA receptors. In agreement with the data from Zimmer et al (), injection of a dihydrokainate into the prefrontal cortex of rats, to block glutamate uptake, was found to be sufficient to drive anhedonia‐like behaviors in multiple studies (Bechtholt‐Gompf et al, ; Cui et al, ; John et al, ; Lee, Gaskins, Anand, & Shekhar, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that depressive phenotypes can be driven by inducing astrocyte dysfunction alone. It was found long‐term NMDA receptor antagonism by memantine, which acts as an open channel blocker (Lipton, ), induced a reduction astrocytic glutamate transport that correlated with a depressive phenotype (Zimmer et al, ). The link between NMDA receptor antagonism and glutamate transporter function in this model of stress is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another consequence of running is the proliferation and growth of astrocytes in the hippocampus of exercised mice (Li et al, 2005;Brockett et al, 2015), which also have lower hippocampal glutamate levels (Biedermann et al, 2012). Anxiety-like behavior is inversely correlated with astrocytic glutamate uptake in the hippocampus (Zimmer et al, 2015), so changes in astrocytic mechanisms involving glutamate in the hippocampus may also mediate decreases in anxiety-like behavior following exercise. Exercise also promotes dendritic growth in the hippocampus (Stranahan et al, 2007), facilitates LTP (van Praag et al, 1999), and affects a wide range of neurotrophic factors, neuropeptides, and neurotransmitters (Bjørnebekk et al, 2006), all of which could potentially affect hippocampal function and alter anxiety-like behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Terms such as neuro- or gliavascular unit (NVU, GVU) describe the strong influence of the microenvironment on the brain endothelium [ 120 ]. Neighboring cell types such as astrocytes, pericytes, microglia, or even neurons are known to influence the functionality of BBB in health as well as in disease, which is supported by their physical proximity and consequent small diffusion distances for signaling molecules [ 120 , 121 ]. Astrocytes can also downregulate microglial activation by secretion of anti-inflammatory substances such as transforming growth factor (TGF) and prostaglandin E2 (PGE2) [ 122 , 123 ], resembling a M2 phenotype, and may thereby limiting neuroinflammation.…”
Section: Reviewmentioning
confidence: 99%